PENERAPAN STRATEGI BELAJAR PETA KONSEP (CONCEPT MAPPING) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 68 TALANG MANDI - Yanti, Yanti; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research is motivated by the lack of a science student learning outcomes can be seen from the results of fourth grade students studied 68 Talang mandi Elementary School, with an average value of 62.11. Therefore, the researchers provide an alternative to the application of the concept map learning strategy in the fourth grade 68 Talang Mandi. This research aims to improve learning outcomes IPA Elementary School fourth grade students Mandau sub 68 Talang Mandi with learning Implementation Strategy Concept Maps. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisis after implementing learning strategies Concept Map, the average percentage of the activity of teachers in the first cycle 58.75% increased to 85% in the second cycle. The average percentage of student activity also increased, namely 51.25% in the first cycle increased to 81.25% in the second cycle. Student learning outcomes in basic score by the average value of 62.11 and the first cycle increased with an average value of 67.42 class with an increasing percentage of learning outcomes 8.54% and the percentage of students who completed 61.53%, and the second cycle increased again by an average of 75.80 with the percentage improvement class learning outcomes 22.04% and the percentage of students who completed 84.61%. These results indicate that the application of learning strategies concept maps can enhance learning outcomes IPA fourth grade students of SD Negeri 68 Talang Mandi.Key words:Learning StrategiesConcept Map, IPALearning Outcomes